Alcohol-Involved Family and Domestic Violence Reported to Police in Australia. Issue 3 (February 2022) - Mayshak, Richelle; Curtis, Ashlee; Coomber, Kerri; Tonner, Lorraine; Walker, Arlene; Hyder, Shannon; Liknaitzky, Paul; Miller, Peter
Family and domestic violence (FDV) is a significant social issue that causes major harm across Australia. Alcohol has been identified as a contributing factor to FDV, and as such increased understanding of the role of alcohol in police-reported FDV incidents may provide the basis for developing specific clinical and forensic approaches. This study aims to identify the key correlates of alcohol-related FDV within police-reported FDV incidence. Data sourced from several states and territories across Australia were used to profile demographic and personal factors involved in police-reported FDV incidents, and to identify the types of incidents involving alcohol. For each state, three separate binary regressions were conducted for family violence, intimate partner violence, and FDV incidents in which alcohol was involved. Between 24% and 54% of FDV incidents reported to police were classified as alcohol-related. Although there appeared to be an association between relative socioeconomic disadvantage and an incident being alcohol-related, this association varied across states. Where victim and offender data were available, offenders were significantly more likely to be alcohol-affected than victims. Alcohol-related FDV incidents were also twice as likely to involve severe physical violence including injuries that were life threatening, as well as an increased likelihood of recidivism. This study demonstrates that alcohol plays a substantial role in police-reported FDV across Australia. It also demonstrates that other factors such as drug use, breach of orders, and repeat offending are associated with alcohol involvement across family violence and intimate partner violence.